A Semantic Programming Language SPL+ - A Preliminary Report - Zhang Guigang; Shu Wang; Xu ChengZhi; Zhiyuan Gong; Sheu, P.C.-Y. (2008 20th IEEE International Conference on Tools with Artificial Intelligence, 2008)
This paper is a preliminary report on the development of a "declarative" programming language SPL+. It assists non-technical people to write programs. The key idea behind SPL+ is that the "programmer" only needs to solve target problems with a standardized methodology without worrying about how to solve the problem efficiently.